Penerapan Metode Penugasan Saintifik dalam Pembelajaran Pendidikan Agama Islam Untuk Meningkatkan Kecerdasan Siswa Kelas X di SMA Nurul Ma’rifah Poncogati - Qoidul Khoir; Ainur Rofiq (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
: The 2013 Curriculum is known as a scientific approach. Scientific approach means a scientific approach that generally involves observation or observation activities needed to collect data. Considerations in choosing the appropriate learning model or method for a particular subject matter are also related to the characteristics that exist in the material. For example, when learning about funeral prayers if a teacher only relies on lecture and expository methods, it is very difficult for students to be able to understand and practice good and correct funeral prayer procedures. The purpose of this study is to describe the steps for applying the scientific assignment method in learning Islamic Religious Education to improve the emotional intelligence of grade X students at SMA Nurul Ma'rifah and the steps for applying the scientific assignment method in learning Islamic Religious Education to improve the spiritual intelligence of grade X students at SMA Nurul Ma'rifah Poncogati. The research method used is a qualitative approach that produces narrative data in the form of natural explanations. The data collection method uses observation, interviews, and documentation. While the analysis method uses interactive model analysis methods. While the presentation of the data by drawing a conclusion, and to obtain the validity of the data using data validity with triangulation techniques. Based on the results of the study, it can be found that the application of scientific assignment methods in learning Islamic Religious Education to improve the intelligence of grade X students at SMA Nurul Ma'rifah Poncogati in improving teachers' emotional intelligence uses 3 scientific assignment methods in the learning process, namely articulation, reciptrocal teaching and inquiry. Meanwhile, in improving spiritual intelligence, teachers use 2 methods, namely habit forming, and memorization